2011
DOI: 10.1088/0957-4484/22/28/285101
|View full text |Cite
|
Sign up to set email alerts
|

Thio-glucose bound gold nanoparticles enhance radio-cytotoxic targeting of ovarian cancer

Abstract: The treatment of ovarian cancer has traditionally been intractable, and required novel approaches to improve therapeutic efficiency. This paper reports that thio-glucose bound gold nanoparticles (Glu-GNPs) can be used as a sensitizer to enhance ovarian cancer radiotherapy. The human ovarian cancer cells, SK-OV-3, were treated by gold nanoparticles (GNPs) alone, irradiation alone, or GNPs in addition to irradiation. Cell uptake was assayed using inductively coupled plasma atomic emission spectroscopy (ICP-AES),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(112 citation statements)
references
References 23 publications
4
108
0
Order By: Relevance
“…Proliferation assays were performed as previously described (Geng et al, 2011). Cells were seeded in a 96-well plate with 200 ml medium, 3-(4,5)-dimethylthiahiazo (-2-y1)-2,5-diphenytetrazoliumromide (MTT, Sigma, St. Louis, MO) was added at a concentration of 0.5 mg/ml, and the cells were incubated for 4 h at 37 C. The medium was removed, and dimethyl sulfoxide (DMSO, Sigma, St. Louis, MO) was added to each well.…”
Section: Measurement Of Cell Proliferationmentioning
confidence: 99%
“…Proliferation assays were performed as previously described (Geng et al, 2011). Cells were seeded in a 96-well plate with 200 ml medium, 3-(4,5)-dimethylthiahiazo (-2-y1)-2,5-diphenytetrazoliumromide (MTT, Sigma, St. Louis, MO) was added at a concentration of 0.5 mg/ml, and the cells were incubated for 4 h at 37 C. The medium was removed, and dimethyl sulfoxide (DMSO, Sigma, St. Louis, MO) was added to each well.…”
Section: Measurement Of Cell Proliferationmentioning
confidence: 99%
“…These finding appear to contradict the physical similarities between the mass energy absorption coefficients of gold and soft tissue using MV radiation sources. Despite this numerous groups have reported significant DEFs using clinical radiation sources delivering MV X-rays (5,(43)(44)(45). The data presented by…”
Section: Gold Nanoparticles (Z=79)mentioning
confidence: 99%
“…In our previous study, we have validated that PEG-Glu-GNPs can enhance the irradiation treatment of solid tumor cells, such as breast cancers, 9 prostate cancers, 30 and ovarian cancer. 11 To compare the therapeutic efficacy of Glu-GNPs with different types of cells, THP-1 and MCF-7 cells were chosen. Note that the breast cancer cell line MCF-7 was selected because it is a commonly used cancer cell line in cancer studies.…”
Section: Characterization Of Nanoparticles and Cellular Uptakementioning
confidence: 99%
“…Many studies have shown that functional nanoparticles are more effective in treating cancers and improving cellular targeting and X-ray irradiation sensitization than nanoparticles alone. 7,[9][10][11] Among these nanoparticles, biocompatible GNPs are the only US Food and Drug Administration (FDA) approved nanomaterials for clinical trials. 12 Many researchers have also shown that GNPs are promising candidates for various biomedical applications in cancer diagnostics and therapeutics.…”
Section: Introductionmentioning
confidence: 99%